TINGKAT ADOPSI TEKNOLOGI PROGRAM PRIMA TANI DAN PENGUATAN KELEMBAGAAN DENGAN PT TRI SARI USAHATANI - Desy Rosita Rahmawati; Lenny Widjayanthi; Sugeng Raharto (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2010)
The purposes of Prima Tani Programs are to socialize agricultural innovation and to reinforce participative rural institutions. One of the innovations from Prima Tani in Paleran village, Umbulsari sub district is hybrid rice Adirasa 1. The role of Gapoktan Eka Jaya is supplying and marketing Hybrid rice Adirasa 1 working together with associate company PT. Tri Sari Usahatani as the producer and distributor the seeds of hybrid rice Adirasa 1. The research location is determined by using purposive sampling method on Paleran village, Umbulsari sub district, Jember regency.The product of district is rice good after Prima Tani stay in Paleran. That indicator is technology adoption level of hybrid rice is better than before. The objectives of this study are to know: (1) farmers’ understanding related to Prima Tani programs; (2) technology adoption level of hybrid rice Adirasa 1; (3) farmer characteristic factors related to technology adoption level of hybrid rice Adirasa 1; (4) innovation features related to technology adoption level of hybrid rice Adirasa 1; (5) the institution role of Gapoktan Eka Jaya in supplying and marketing the rice yields with TST through Gapoktan. Key Words: Technology adoption level, Prima Tani programs, the institution role, Adirasa I .